THE DEVELOPMENT OF A CONCEPTUAL QUALITY ASSURANCE MANAGEMENT MODEL FOR THE IMPLEMENTATION OF THE NEWLY REVISED MS1500:2019 HALAL FOOD-GENERAL REQUIREMENTS - Abu Karim, Rizuwan; Wan Mohamad Saferdin, Wan Aisyah Amni; Aziz, Anidah; Abu Bakar, Norida; Ab Kadir, Mohd Sufian; Azis, Siti Noraziana; Ayob, Mastura (Jurnal ’Ulwan, 2022)
The purpose of this study is to propose a conceptual quality assurance management model for the newly revised version of Halal food standards known as MS1500:2019 Halal Food-General Requirements. Every five years The MS1500 need to be revised because it will ensure the general guideline in producing halal food product will be relevant to the Halal ecosystem. But, the revision of the MS1500:2009 – Production, Preparation, Handling and Storage of halal food standard was overdue in five years. Even though the standard has been revised, but media massa still reported some halal food product with halal certification sold in the market was failed to fulfil the MS1500:2009 requirements. Thus, this paper aims to propose a conceptual quality assurance management model which may assure Shariah compliance of halal food. Systematic literature review methodology has been used to identify the most commonly used variables in the literature. Findings shows that the recommended framework in this study consists of total quality management (TQM) practices which may serve as a variable to implement the MS1500:2009 Hence, there should be a continuous cooperation between the policy makers and food manufacturers on how to effectively implement such framework.